Nitrogen-Doped Graphene Foam as a Metal-Free Catalyst for Reduction Reactions under a High Gravity Field. (June 2020) - Wang, Zhiyong; Zhao, Zhijian; Baucom, Jesse; Wang, Dan; Dai, Liming; Chen, Jian-Feng
Abstract: Herein, we report on the effect of a high gravity field on metal-free catalytic reduction, taking the nitrobenzene (NB) reduction and methylene blue (MB) degradation as model reactions in a high-gravity rotating tube reactor packed with three-dimensional (3D) nitrogen-doped graphene foam (NGF) as a metal-free catalyst. The apparent rate constant ( k app ) of the metal-free catalytic reduction of NB in the rotating tube reactor under a high gravity level of 6484 g ( g  = 9.81 m·s −2 ) was six times greater than that in a conventional stirred reactor (STR) under gravity. Computational fluid dynamics (CFD) simulations indicated that the improvement of the catalytic efficiency was attributed to the much higher turbulent kinetic energy and faster surface renewal rate in the high-gravity tube reactor in comparison with those in a conventional STR. The structure of the 3D metal-free catalysts was stable during the reaction process under a high gravity field, as confirmed by X-ray photoelectron spectroscopy (XPS) and Raman spectra. In the other model reaction, the rate of MB degradation also increased as the high gravity level increased gradually, which aligns with the result for the NB catalytic reduction system. These results demonstrate the potential to use a high-gravity rotating packed tube reactor for the process intensification of metal-free catalytic reduction reactions.